Perspektif Hukum Era Digital terhadap Wanprestasi dalam Perjanjian Sewa Menyewa Alat Berat - Nurul Rachma Tiyas (Jurnal Hukum Lex Generalis, 2025)
The digital era has brought significant changes in the implementation and settlement of defaults in heavy equipment leasing agreements in Indonesia, especially regarding the validity of documents and electronic signatures. This study examines the implications of using digital technology in heavy equipment lease contracts as well as the role of regulation and legal literacy in overcoming default obstacles. The results of the study show that electronic documents and digital signatures have legal validity based on the ITE Law and its amendments, but challenges such as lack of understanding of business actors, limited digital technology infrastructure, and data security are still the main obstacles. Adaptive and specific regulations and improved legal literacy are key factors in strengthening legal certainty and minimizing disputes. In addition, the application of new technologies such as blockchain and digital dispute resolution platforms can improve the efficiency and transparency of the process. This research recommends strengthening derivative regulations, improving legal education, and developing equitable digital technology infrastructure to support a safe and reliable contract ecosystem. Thus, the digital era has the potential to encourage the growth of a more sustainable and highly competitive construction and heavy equipment leasing sector.